Looking on the Bright Side of Stigma: How Stress-related Growth Facilitates Adaptive Coping among Gay and Bisexual Men. - Wang, Katie; Rendina, H Jonathon; Pachankis, John E (Journal of gay & lesbian mental health, 2016)
Stigma has been linked to adverse mental health outcomes among gay and bisexual men, yet how psychological resources facilitate adaptive coping remains unclear. The present study examined the association between stress-related growth and internalizing mental health symptoms and considered emotion regulation as a mechanism mediating this association. Gay and bisexual men completed questionnaires measuring stress-related growth associated with sexual orientation identity development, emotion regulation difficulties, and anxiety and depressive symptoms. Stress-related growth was associated with more effective emotion regulation, which in turn predicted fewer internalizing symptoms. These findings have important implications for understanding and alleviating sexual minority mental health disparities.